2004
DOI: 10.1007/s10201-004-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biomass and spatial distribution of Elodea nuttallii (Planch.) St. John, an invasive submerged plant, in oligomesotrophic Lake Kizaki from 1999 to 2002

Abstract: Distribution of pure Elodea nuttallii vegetation was surveyed from 1999 to 2002, immediately after the most recent expansion of the species in Lake Kizaki, Japan. During 2001 and 2002, areas of E. nuttallii vegetation rapidly diminished and the summer plant height decreased wherever the vegetation remained. The organic matter content, total phosphorus, and extracted P of the sediment from the vegetation bed were measured. A linear relationship was observed between the extracted P in the sediment and the biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
8
21
0
Order By: Relevance
“…At the present loading rate, biomass of the submerged vegetation (modeled according to Elodea characteristics) was negligible, but the model calculated a maximum biomass of 90 g m -2 at reduced loading levels in combination with a marsh surface area of 15% or higher. This maximum biomass is comparable to empirical results of the study of Nagasaka (2004), in which Elodea nuttallii biomass ranged between 20 and 150 g m -2 in a shallow littoral zone. Immediately after significant growth of the submerged vegetation, in the model chlorophyll-a levels dropped from 0.057 mg l -1 to 0.002 mg l -1 , due to a positive feedback loop of improved light conditions, improved plant growth, reduced nutrient levels, decreased algal biomass, improved light conditions and so on.…”
Section: Nutrient Retention Processessupporting
confidence: 86%
“…At the present loading rate, biomass of the submerged vegetation (modeled according to Elodea characteristics) was negligible, but the model calculated a maximum biomass of 90 g m -2 at reduced loading levels in combination with a marsh surface area of 15% or higher. This maximum biomass is comparable to empirical results of the study of Nagasaka (2004), in which Elodea nuttallii biomass ranged between 20 and 150 g m -2 in a shallow littoral zone. Immediately after significant growth of the submerged vegetation, in the model chlorophyll-a levels dropped from 0.057 mg l -1 to 0.002 mg l -1 , due to a positive feedback loop of improved light conditions, improved plant growth, reduced nutrient levels, decreased algal biomass, improved light conditions and so on.…”
Section: Nutrient Retention Processessupporting
confidence: 86%
“…Reduced biomass increment observed in our experiment suggested the plant growth was inhibited. Noticeable declines of E. nuttallii populations in Japan (NAGASAKA 2004) and Elodea canadensis in Europe (SCULTHORPE 1967) were reported, and scientists have suggested different stress (biotic and abiotic) factors regarding this decline (HAMABATA 1991, KADONO et al 1997. Our results also supported by BRIX and SORRELL (1996), who reported that wetland plants grown in reducing treatments stopped growing, some of them losing mass.…”
Section: +2supporting
confidence: 84%
“…The results about littoral macrophytes are similar to the descriptions of mountain lakes; where the macrophytes are present contributing a high oxygen concentration (Nagasaka, 2004;Li et al, 2009). The high amount of species in Tinquilco Lake would be probably related to the transition from oligotrophy to mesotrophy observed in this lake (De los Ríos et al, 2007), these patterns are similar to other lakes of the same category, with changes in trophic status, where ultraoligotrophic lakes have a low amount of species and abundance (Nagasaka, 2004;Li et al, 2009).…”
Section: ___________________supporting
confidence: 80%
“…Nevertheless, an oligotrophy to mesotrophy transition has been observed in some lakes located mainly between 38 to 41°S, due to the replacing of the native forest of their basin by agricultural zones, towns and industries (Soto, 2002). One of the biotic components that can be an indicator of trophic status is the assemblage of macrophytes (Hauenstein et al, 2002;Nagasaka, 2004;Li et al, 2009). We define macrophytes according to Ramírez & Stegmeier (1982).…”
Section: ___________________mentioning
confidence: 99%